On a Deterministic Approximation of Inventory Systems with Sequential Service-Level Constraints - Wei, Lai; Jasin, Stefanus; Xin, Linwei (Operations Research, 2021)
Solving Inventory Models with Service-Level Constraints by Using a Deterministic Approximation